The Role of Training and Promotion to Increase The 3rd Party Funds Indonesian Islamic Banking - Rahmat Hidayat; Agus Maolana Hidayat (Tazkia Islamic Finance and Business Review, 2013)
Objective – This study aims to determine whether the role of training is much larger than the promotion in raising third-party funds in Islamic banks in Indonesia given the cost of the training is spent is greater than the cost of promotion. This study empirically examines the relationship and impact of training and promotion to raise funds for a 3rd party in Indonesia Islamic banks.Methods – This study uses secondary data Islamic commercial banks in the form of panel (time-series and cross-section) of Bank Indonesia data from 2010 until 2012. There are two independent variables training cost (X1) and promotion cost (X2) and one dependent variable is 3rd-party funds (Y). The analysis technique used path analysis to examine the role of training and the promotion of financial performance (The 3rd Party Funds).Result – Simultaneously, training and promotion gives an effect by 52%, and partially or individual training gives an insignificant negative effect, while the promotion has a significant positive impact on financial performance (financial-party funds) on Islamic banking.Conclusion – The role of promotion is higher in raising The 3rd Party Funds than training. Keywords : Cost, Training, Promotion, The 3rd Party Funds